Parabolic Trough System Operating with Nanofluids: Comparison with the Conventional Working Fluids and Influence on the System Performance. (November 2016) - Ferraro, V.; Settino, J.; Cucumo, M.A.; Kaliakatsos, D.
Abstract: To analyse the behaviour of a parabolic trough operating with nanofluids, and compare its performance to the more traditional ones using oil, a model for the thermal analysis of the system has been developed and implemented in Matlab. The simulations have been performed for a suspension of Al2 O3 in synthetic oil and its characteristics compared to the corresponding basic liquid used by itself. The string has been assumed to have a length of 100 m and a concentrating surface area of 550 m 2 . The simulations have been carried out for different DNI (Direct normal irradiance) and variable mass flow, ensuring a temperature at the collector outlet below 400̊C. For a proper comparison, the following variables and efficiency indicators have been checked: power output, pumping power, thermal efficiency and overall efficiency of the parabolic trough system.